Changing “Al-Munkar” between Arabic and Sharia: An Analytical Study - Menacer, Nacira; Bechiri, Ammar (Milev Journal of Research and Studies, 2021)
This study aims to clarify the cognitive integration between Arabic and Sharia based on the term “Al-Munkar”; which is a term used in. It also seeks to establish the term “linguistic Munkar” by comparing data in Arabic and Sharia. The research plan included the following elements: definition of the term “linguistic Munkar”; comparing data of “Al-Munkar” in Arabic and Sharia; levels of changing “Al-Munkar” between Arabic and Sharia. The study reached a set of results. The most important is that the great similarity between data in Arabic and Sharia allowed to give an construction for the term “linguistic Munkar